SPECIFICITY OF VOCAL AND CHORAL SKILLS FORMATION STUDENTS OF SENIOR CLASSES OF MUSIC SCHOOLS (Pedagogy of Higher and Secondary Education, 2009)
Different approaches dealing with formulating pupils' of the last forms vocal-chorus abilities in the classes of chorus in the condition of musical school are considered in this article. The main notions are defined and the peculiarities of accomplishment of vocal-chorus exercises are based.